Cultural Heritage: An Introduction to Entanglements of Knowledge, Politics and Property - Kristin Kuutma (Journal of Ethnology and Folkloristics)
Heritage is today actively implemented in policies globally, and yet the categorisation and instrumentalisation of the realm of cultural heritage entails rather contradictory aspects. In the discourse of culture, heritage is an abstraction, and what it signifies is subject to interpretation. This contribution gives a brief overview of the contemporary discussion of the epistemological and ontological premises of cultural heritage. It has been stated that heritage is a social construction, and a mode of cultural production that emanates from a metacultural relationship. The critical assessment and theorisation of heritage includes an enquiry into tangible and intangible heritagisation, knowledge production, heritage politics, and the question of ownership.